Evaluation of 5‐year imatinib treatment of 458 patients with CP‐CML in routine clinical practice and prognostic impact of different BCR‐ABL cutoff levels. (21st February 2013) - Klamová, Hana; Poláková, Kateřina Machová; Mužík, Jan; Ráčil, Zdeněk; Žáčková, Daniela; Steinerová, Kateřina; Karas, Michal; Faber, Edgar; Demečková, Eva; Michalovičová‐Sninská, Zuzana; Voglová, Jaroslava; Demitrovičová, Ľudmila; et al.
Abstract We evaluated responses to the treatment and long‐term outcomes of chronic myeloid leukemia patients treated with imatinib as first‐line treatment in routine clinical setting from two countries with centralized tyrosine kinase inhibitors (TKIs) treatment. We assessed prognostic significance of European LeukemiaNet (ELN) 2006‐ and 2009‐defined responses and the prognostic value of molecular responses at defined time points on 5‐year survivals. Among the cumulative rates of incidence of hematologic, cytogenetic, and molecular responses and all important survival parameters, we evaluated the prognostic significance of different BCR‐ABL transcript‐level ratios (≤1%; >1%–≤10%; >10%) at 3, 6, 12, and 18 months (n = 199). The ELN optimal response criteria and their predictive role were significantly beneficial for event‐free survival at all given time points. We found significant improvement in survivals of patients with BCR‐ABL lower than 10% in the 6th and 12th months. Significantly better outcome was found in patients who achieved major molecular response (MMR) in the 12th month. The cumulative incidences of complete cytogenetic response (CCyR) and MMR were significantly associated with the molecular response in the 3rd month. The ELN response criteria and their predictive role were helpful at given time points; however, the 2009 definition did not significantly alter the prognostic accuracy compared with that of the 2006 definition. The significant value was observed for cytogenetic responses at the 6th and 12th month. Moreover, progression‐free and event‐free survivals were improved with MMR at the 12th month.